The Mirage of Digital Communication and the Danger Brought by the Explosion of Digital Technology - Popa, Doinița (Journal of Danubian Studies and Research, 2023)
The paper presents aspects of the significant impact that digital communication has on society, and the advantages, such as quick access to information, global connectivity, and the ability to interact with people around the world. Nevertheless, with the explosion of digital technology, certain dangers and challenges have also arisen. One of the main dangers of digital communication is the lack of privacy and data security; the spread of misinformation and fake news can have severe consequences for society, from influencing public opinion to affecting democracy and political stability. Also, excessive reliance on digital technology can lead to social isolation and diminished interpersonal communication skills. It is essential to be aware of these risks and take steps to minimize them.